Unraveling the Myths of Rural vs. Urban Academic Achievement Drivers - Beatriz-Afonso, Ana (2024)
Beatriz-Afonso, A., & Cruz-Jesus, F. (2024). Unraveling the Myths of Rural vs. Urban Academic Achievement Drivers. Emerging Science Journal, 8(6), 2312-2327. Article 10. https://doi.org/10.28991/ESJ-2024-08-06-010 --- This work was supported by national funds through FCT (Fundação para a Ciência e a Tecnologia), under the project UIDB/04152/2020- Centro de Investigação em Gestão de Informação (MagIC)/NOVA IMS) (doi:10.54499/UIDB/04152/2020).